ANALYSIS OF THE COMPLEXITY OF TE WAZA TECHNIQUES OF JUDO BELONGING TO GOKYO - Fernando Ikeda Tagusari; Fernando Garbeloto dos Santos; Go Tani (Journal of Physical Education)
ABSTRACT Assuming that the Gokyo is a guide for the teaching process of judo techniques it is reasonable to infer that it must be organized following a growing order in relation to the complexity of the techniques between the series. Based on the concept of task complexity drawn from motor learning literature the objective of this study was to analyze the Te waza techniques of Gokyo to verify if they are organized according to growing order of complexity. Complexity was defined as the number of components and their interactions. The choice of these techniques was based on a more homogeneous distribution among Gokyo series. The result found was that 66% of the techniques of Te waza are organized in accordance with the growing order of complexity defined by the application of criteria of the motor learning area.